Effects of various food ingredients on gall bladder emptying - Marciani, Luca; Cox, Eleanor; Hoad, Caroline; Totman, John J.; Costigan, C.; Singh, Gulzar; Shepherd, V.; Chalkley, L.; Robinson, M.; Ison, R.; Gowland, Penny A.; Spiller, Robin C. (Nature Publishing Group, 2013)
Background/objectives: The emptying of the gall bladder in response to feeding is pivotal for the digestion of fat, but the role of various food ingredients in contracting the gall bladder postprandially is not well understood. We hypothesized that different food ingredients, when consumed, will have a different effect on stimulating gall bladder emptying. To investigate this we designed two randomized, investigator-blind, cross-over studies in healthy subjects using magnetic resonance imaging (MRI) to measure gall bladder volumes serially and non-invasively.